Strengthening agricultural education and training in Sub-Saharan Africa from an innovation systems perspective: Case studies of Ethiopia and Mozambique - Davis, Kristin E.; Ekboir, Javier; Mekasha, Wendmsyamregne; Ochieng, Cosmas M. O.; Spielman, David J.; Zerfu, Elias (International Food Policy Research Institute, 2007)
This paper examines the role of postsecondary agricultural education and training (AET) in Sub-Saharan Africa in the context of the region’s agricultural innovation systems. Specifically, the paper looks at how AET in Sub-Saharan Africa can contribute to agricultural development by strengthening innovative capabilities, or the ability to introduce new products and processes that are socially or economically relevant to smallholder farmers and other agents in the agricultural sector. Using AET in Ethiopia and Mozambique as case studies, the paper argues that while AET is conventionally viewed in terms of its role in building human and scientific capital, it also has a vital role to play in building the capacity of organizations and individuals to transmit and adapt new applications of existing information, new products and processes, and new organizational cultures and behaviors. The paper emphasizes the importance of improving AET systems by strengthening the innovative capabilities of AET organizations and professionals; changing organizational cultures, behaviors, and incentives; and building innovation networks and linkages. The paper draws on two main sources of information: the emerging literature on innovation systems in developing-country agriculture, and data gathered from secondary sources and semi-structured key informant interviews conducted in Ethiopia and Mozambique in late 2006. The paper offers several recommendations that can contribute to enhancing the effectiveness of AET’s contribution to agricultural innovation and development. Key reforms include aligning the mandates of AET organizations with national development aspirations by promoting new educational programs that are more strategically attuned to the different needs of society; inducing change in the cultures of AET organizations through the introduction of educational programs and linkages beyond the formal AET system; and strengthening individual and organizational capacity by improving incentives to forge stronger linkages between AET and diverse user communities, knowledge sources, and private industry." - from authors' abstract.